Gluteal Compartment Syndrome following an Iliac Bone Marrow Aspiration - Edmundo Berumen-Nafarrate; Carlos Vega-Najera; Carlos Leal-Contreras; Irene Leal-Berumen (Case Reports in Orthopedics)
The compartment syndrome is a condition characterized by a raised hydraulic pressure within a closed and non expandable anatomical space. It leads to a vascular insufficiency that becomes critical once the vascular flow cannot return the fluids back to the venous system. This causes a potential irreversible damage of the contents of the compartment, especially within the muscle tissues. Gluteal compartment syndrome (GCS) secondary to hematomas is seldom reported. Here we present a case of a 51-year-old patient with history of a non-Hodgkin lymphoma who underwent a bone marrow aspiration from the posterior iliac crest that had excessive bleeding at the puncture zone. The patient complained of increasing pain, tenderness, and buttock swelling. Intraoperative pressure validation of the gluteal compartment was performed, and a GCS was diagnosed. The patient was treated with a gluteal region fasciotomy. The patient recovered from pain and swelling and was discharged shortly after from the hospital. We believe clotting and hematologic disorders are a primary risk factor in patients who require bone marrow aspirations or biopsies. It is important to improve awareness of GCS in order to achieve early diagnosis, avoid complications, and have a better prognosis.